2011
DOI: 10.1182/blood-2011-02-339747
|View full text |Cite
|
Sign up to set email alerts
|

TET2 mutation is an unfavorable prognostic factor in acute myeloid leukemia patients with intermediate-risk cytogenetics

Abstract: The studies concerning clinical implications of TET2 mutation in patients with primary acute myeloid leukemia (AML) are scarce. We analyzed TET2 mutation in 486 adult patients with primary AML. TET2 mutation occurred in 13.2% of our patients and was closely associated with older age, higher white blood cell and blast counts, lower platelet numbers, normal karyotype, intermediate-risk cytogenetics, isolated trisomy 8, NPM1 mutation, and ASXL1 mutation but mutually exclusive with IDH mutation. TET2 mutation is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
191
4
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 274 publications
(210 citation statements)
references
References 48 publications
8
191
4
7
Order By: Relevance
“…(Chou, et al 2011a, Metzeler, et al 2011 In our study of AML patients with and without chromosomal abnormalities, TET2 mutation was also found to be positively associated with normal karyotype, intermediate-risk cytogenetics, isolated trisomy 8, NPM1 mutation, and ASXL1 mutation. (Chou, et al 2011a) In European LeukemiaNet (ELN) favorable-risk group (patients with CN-AML with mutated CEBPA and/or mutated NPM1 without FLT3-ITD), (Dohner, et al 2010) but not intermediate-1 risk group (CN-AML with wild-type CEBPA and wild-type NPM1 and/or FLT3-ITD), TET2-mutated patients were found to have a lower CR rate, shorter DFS and OS, compared with TET2-wild type patients. (Metzeler, et al 2011) However, we did not have the same finding, but found that TET2 mutation was an unfavorable prognostic factor in patients with intermediate-risk cytogenetics, and its negative impact was further enhanced when the mutation was combined with FLT3-ITD, NPM1-wild, or unfavorable genotypes (other than ELN favorable-risk group).…”
Section: Tet2 Mutationssupporting
confidence: 53%
See 2 more Smart Citations
“…(Chou, et al 2011a, Metzeler, et al 2011 In our study of AML patients with and without chromosomal abnormalities, TET2 mutation was also found to be positively associated with normal karyotype, intermediate-risk cytogenetics, isolated trisomy 8, NPM1 mutation, and ASXL1 mutation. (Chou, et al 2011a) In European LeukemiaNet (ELN) favorable-risk group (patients with CN-AML with mutated CEBPA and/or mutated NPM1 without FLT3-ITD), (Dohner, et al 2010) but not intermediate-1 risk group (CN-AML with wild-type CEBPA and wild-type NPM1 and/or FLT3-ITD), TET2-mutated patients were found to have a lower CR rate, shorter DFS and OS, compared with TET2-wild type patients. (Metzeler, et al 2011) However, we did not have the same finding, but found that TET2 mutation was an unfavorable prognostic factor in patients with intermediate-risk cytogenetics, and its negative impact was further enhanced when the mutation was combined with FLT3-ITD, NPM1-wild, or unfavorable genotypes (other than ELN favorable-risk group).…”
Section: Tet2 Mutationssupporting
confidence: 53%
“…(Bacher, et al 2010, Couronne, et al 2010, Flach, et al 2010, Jankowska, et al 2009, Kosmider, et al 2009a, Kosmider, et al 2009b, Langemeijer, et al 2009, Saint-Martin, et al 2009, Schaub, et al 2010, Smith, et al 2010, Tefferi, et al 2009a, Tefferi, et al 2009b TET2 mutation occurs in 18.0% to 23% of CN-AML patients. (Chou, et al 2011a, Metzeler, et al 2011 It is closely associated with older age, higher WBC count, but mutually exclusive with IDH mutation. (Chou, et al 2011a, Metzeler, et al 2011 In our study of AML patients with and without chromosomal abnormalities, TET2 mutation was also found to be positively associated with normal karyotype, intermediate-risk cytogenetics, isolated trisomy 8, NPM1 mutation, and ASXL1 mutation.…”
Section: Tet2 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest an adverse impact of TET2 mutations on outcome in certain AML subgroups; in other studies, no prognostic significance was found [47][48][49][50].…”
Section: Tet2mentioning
confidence: 99%
“…Mutations of the TET2 gene have been found in various myeloid malignancies; 8-27 % of AML, 20-25 % of MDS, 4-13 % of MPN [31,32,[46][47][48][49]. TET2 mutations are loss-of-function of mono allele in most cases, including missense, frameshift and nonsense mutations.…”
Section: Tet2mentioning
confidence: 99%